Muslims and Arabs in Western Politics (American Journal of Islam and Society, 2005)
The “Muslims and Arabs in Western Politics” conference, held at IndianaUniversity, Bloomington, on September 22-24, 2005 and organized byAbdulkader Sinno (assistant professor, political science and Middle Easternstudies, Indiana University), was highly enriching and intellectually stimulating.The two public lectures and five panels, ranging from civil rights and libertiesto public perceptions of Muslims, shed light on various aspects of thecomplexities of this field and acquainted the participants with cutting-edgeresearch by leading scholars from North America and Western Europe.James Zogby and David Cole delivered the two public lectures on “TheEmergent Arab-American Political Constituency” and “Paradigms ofPrevention: The Rule of Law and the War on Terror,” respectively. Zogby covered the development of the Arab-American community’s politicalmobilization and inclusion in mainstream American politics throughout thetwentieth century. He narrated his personal experience as a Lebanese immigrantwho had experienced the “hard times” of discrimination and exclusion.In addition, he reported on the significant increase in the political mobilizationof Muslim minorities in the United States over the last few decades,combined with a growing interest from politicians. His speech ended on apositive note: He is convinced that the community’s trajectory will continueto move forward. On the other hand, David Cole’s talk focused on the stateof constitutional law after 9/11. He argued that substantial negative inroadshave been made to the five pillars of the rule of law, namely, equality beforethe law, transparency of procedures, fairness of procedures, checks and balances,and commitment to basic human rights ...